Technical and Vocational Education and Training in Federal Nepal: A Critical Analysis - Bhandari, Usha (Journal of Technical and Vocational Education and Training, 2023)
The technical and vocational education and training (TVET) in Nepal is one of the much discussed agenda for its contribution to socio-economic development of the country. Historically, Nepal’s TVET system is striving for being innovative and compatible with the global trends. With the Nepal’s Constitution 2015, it has received a considerable attention, as the Constitution (in article 51, h, 1) highlights the notion of TVET along with the allocation of TVET responsibilities to all three tiers of government. However, due to differing understanding among the policy makers, including existing several issues and concerns, the development of TVET sector in Nepal has been slow off the mark. Yet, Nepal has many opportunities for reforming the TVET sector in the coming days. There is an urgent need of paradigm shift in action, thoughts and visions in line with the Constitution to harness the benefit of TVET sector - to achieve the goal of socio-economic prosperity of the country.